Impact of body composition, nutritional and inflammatory status on outcome of non-small cell lung cancer patients treated with immunotherapy. (June 2021) - Baldessari, Cinzia; Guaitoli, Giorgia; Valoriani, Filippo; Bonacini, Riccardo; Marcheselli, Raffaella; Reverberi, Linda; Pecchi, Annarita; Menozzi, Renata; Torricelli, Pietro; Bertolini, Federica; Barbieri, Fausto; Dominici, Massimo
Summary: Background and aims: Body composition and balance of nutritional and inflammatory status are important for the immune system. Alterations of these aspects may impact on response, outcome and toxicities of immunotherapy. In this review we try to clarify some definitions and tools used for the assessment of the different aspects of nutritional disorders, body composition and inflammatory status with a focus on lung cancer. Methods: We primary investigate the definitions of malnutrition, cachexia, sarcopenia and overweight. Secondary, tools used to measure body composition, nutritional and inflammatory status, mainly in lung cancer are reviewed. Results: All these features, in the time of precision medicine may improve assessment and selection of patients, incorporating also early palliative care in standard therapy. Conclusions: A multimodal approach based on nutrition assessment and physical exercise should be evaluated to improve aspects of the immune response against cancer and to propose the best treatment to every patient. Graphical abstract: Image 1 Highlights: Malnutrition, cachexia, sarcopenia and obesity on cancer patients deserve attention. Different tools, both single one and scoring system, can be used to measure them. They have impact on patient's outcome and attract interest in immunotherapy era. We focus on lung cancer patients treated with immunotherapy.